Chapter Raccontare, raccontarsi. Massimo Quaini fra biografia ed 'egogeografia' - Rossi, Luisa (Territori, 2021)
Intertwining biographical method and autobiography. Massimo Quaini had shown much interest in the 'egogeography' genre, practiced by different French geographers. The work traces back, on the basis of published and unpublished writings, some significant aspect of the intellectual personality of the Italian geographer. In particular, passages are presented in which he recalls his scientific and professional training and some letters that account for the highly critical positioning towards academic power, against the management of competitions based on personal relationships rather than on scientific merits (to the detriment of the discipline itself). Some original documents testify the interest in history and philosophy and the acceptance of historical materialism that has shaped his youth work and, more generally, founded his interpretation of geographical reality.